Search for a W ' boson decaying to a muon and a neutrino in pp collisions at root s=7 TeV - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (Elsevier B.V., 2011)
A new heavy gauge boson, W', decaying to a muon and a neutrino, is searched for in pp collisions at a centre-of-mass energy of 7 TeV. The data, collected with the CMS detector at the LHC, correspond to an integrated luminosity of 36 pb(-1). No significant excess of events above the standard model expectation is found in the transverse mass distribution of the muon-neutrino system. Masses below 1.40 TeV are excluded at the 95% confidence level for a sequential standard-model-like W'. The W' mass lower limit increases to 1.58 TeV when the present analysis is combined with the CMS result for the electron channel. (C) 2011 CERN. Published by Elsevier B.V. All rights reserved.
Keywords: CMS; Physics; Software; Computing